Wat beteken "kanon" vandag? - Venter, P. M. (Hervormde teologiese studies, 1998)
What does 'canon' mean at present? The notion of canon has become quite complicated. In textual criticism it is no longer possible to identiy the canon with only one form of the textual tradition. Canonical texts originate and function in communities of faith. Childs' canonical approach does not accommodate this aspectproperly. Sanders' canon criticism invites social scientific criticism like Gottwald's to enable one to understand the canon within a much largerframe work. Even traditional studies of the history of the canon have to pay attention to a series of sociocultural factors. In postmodern society the canon of the Bible works on a multidimensional level, conrontingpeople with the living God who empowers them to live in God's presence.